A comparison between Australian and US populations on attitudes to criminal behaviours. Issue 2 (7th February 2022) - De Soto, William; Wiener, Karl Kilian Konrad; Tajalli, Hassan; Brookman, Ruth
ABSTRACT: Purpose . This study compares the attitudes of American and Australian general populations on a continuum of punitive-rehabilitative attitudes toward various criminal offences, in order to test the theory of American Exceptionalism. Method . The data for the study were collected via an online survey of the American and Australian public. Six criminal scenarios were presented to the respondents in order to assess the differences of attitudes of men and women between and within the two countries. Results . Australians show greater punitive attitudes than their American counterparts for drug related offences only, whilst there were no differences for other offences. A gender comparison shows that Australian men are more punitive for criminal acts of robbery, burglary, and drug related offences, while American men are more punitive for criminal acts of robbery and burglary. People's fear of crime increases punitive attitudes for criminal acts of burglary and drug related offences. Conclusion . Overall, the findings do not support the hypothesis of American Exceptionalism. The findings suggest that people's punitive attitudes are complex and differ when considering various offence types across both countries and genders. Future research in this area needs to consider offence types as an important variable when exploring punitive attitudes.